LEARNING STRATEGIES TO IMPROVE THINKING ABILITIES - Mariska, Dea; Hakim, Habibul; Dina Septiana, Yulda (Amanah Publishing, 2025)
Being a teacher is not easy. To ensure that learning objectives are achieved, we must employ a variety of strategies. This study aims to examine various effective learning strategies for improving students' thinking skills, including critical, analytical, and creative thinking. The method used was library research, where various academic literature and empirical studies related to learning strategies were analyzed to gain insight into the most relevant approaches. The results showed that student-centered learning strategies, such as project-based learning, group discussions, and collaborative problem-solving, can significantly improve students' thinking skills. This occurs because these methods encourage students to think more deeply, solve problems independently, and collaborate in understanding complex concepts. The implications of these findings suggest that educational institutions that implement these strategies can develop students' thinking skills more effectively, which in turn will improve their academic performance and readiness to face real-world challenges.